Cobalt–Nitrogen‐Doped Helical Carbonaceous Nanotubes as a Class of Efficient Electrocatalysts for the Oxygen Reduction Reaction. (4th September 2018) - Liang, Zuozhong; Fan, Xing; Lei, Haitao; Qi, Jing; Li, Youyong; Gao, Jinpeng; Huo, Meiling; Yuan, Haitao; Zhang, Wei; Lin, Haiping; Zheng, Haoquan; Cao, Rui
Abstract: The oxygen reduction reaction (ORR) is of significant importance in the development of fuel cells. Now, cobalt–nitrogen‐doped chiral carbonaceous nanotubes (l/d ‐CCNTs‐Co) are presented as efficient electrocatalysts for ORR. The chiral template, N‐stearyl‐l/d ‐glutamic acid, induces the self‐assembly of well‐arranged polypyrrole and the formation of ordered graphene carbon with helical structures at the molecular level after the pyrolysis process. Co was subsequently introduced through the post‐synthesis method. The obtained l/d ‐CCNTs‐Co exhibits superior ORR performance, including long‐term stability and better methanol tolerance compared to achiral Co‐doped carbon materials and commercial Pt/C. DFT calculations demonstrate that the charges on the twisted surface of l/d ‐CCNTs are widely separated; as a result the Co atoms are more exposed on the chiral CCNTs. This work gives us a new understanding of the effects of helical structures in electrocatalysis. Abstract : Cobalt‐Stickstoff‐dotierte links‐ oder rechtsgängige chirale Kohlenstoff‐Nanoröhren (l/d ‐CCNTs‐Co) wurden mit N ‐Stearyl‐l/d ‐glutaminsäure als Templat synthetisiert. Der helikale Katalysator stellt ein Übergangsmetall‐Stickstoff‐Kohlenstoff‐System für die Sauerstoffreduktion dar.